2006
DOI: 10.1007/s11095-005-8925-x
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity and Mechanism of the Intestinal Clonidine Uptake by Caco-2 Cells

Abstract: Clonidine is transported by a carrier-mediated process. Substrate specificity and mechanism are very similar to the transport described in blood-brain barrier endothelial cells. The transport characteristics do not correspond to carriers for organic cations of the SLC22 family or the choline transporters CHT1 and CLT1. The system might be identical to the H+/tertiary amine antiporter. It interacts with a large number of both hydrophilic and lipophilic cationic drugs, and also, interestingly, with opiates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
(33 reference statements)
0
14
1
Order By: Relevance
“…An analogous nicotine/proton antiporter has also been characterized in kidney tubules, Caco-2, JAR, and LLC-PK1 cell lines (8,36,37). Many cationic organic drugs, such as clonidine, diphenhydramine, and MDMA, are similarly transported by a proton antiporter in Caco-2 cells (38)(39)(40). The trans-stimulation of the BBB transport of nicotine by diphenhydramine, naloxone, or tramadol suggests that they share the same transporter.…”
Section: Discussionmentioning
confidence: 96%
“…An analogous nicotine/proton antiporter has also been characterized in kidney tubules, Caco-2, JAR, and LLC-PK1 cell lines (8,36,37). Many cationic organic drugs, such as clonidine, diphenhydramine, and MDMA, are similarly transported by a proton antiporter in Caco-2 cells (38)(39)(40). The trans-stimulation of the BBB transport of nicotine by diphenhydramine, naloxone, or tramadol suggests that they share the same transporter.…”
Section: Discussionmentioning
confidence: 96%
“…However, studies on the transport of secondary or tertiary amine drugs, such as methylenedioxymethamphetamine (MDMA, ecstasy), oxycodone, and clonidine, led to the discovery of an H + antiporter that is not inhibited by TEA. Its functional properties differ from those of any of the already identified organic cation transporters (Fischer et al, 2006;Okura et al, 2008;Kuwayama et al, 2008). However, as the molecular nature of the transporter involved has not been identified, it is commonly known as the 'tertiary or secondary amine/H + ' antiporter.…”
Section: Introductionmentioning
confidence: 91%
“…Methylenedioxymethamphetamine is one of them and its transport was inhibited by DPHM in a concentration‐dependent manner 8. Oxycodone, a tertiary amine, and clonidine were also found to be transported by this H + antiporter, which has different functional properties than previously known organic cation transporters (OCTs) 9,10. Andre et al11 suggested that clonidine transport across the luminal BBB involves a distinct amine/H + antiporter, and that this transporter interacts with organic compounds that have secondary or tertiary amine moieties.…”
Section: Introductionmentioning
confidence: 92%